Kedudukan Penyidik Kepolisian Terhadap Kewenangannya Menangani Perkara Tindak Pidana Korupsi Penyalahgunaan Wewenang Menurut Perspektif Sistem Peradilan Pidana - Ulhaq, A Mahbub (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This paper focuses on the role and challenges of Polri investigators in the Indonesian criminal justice system, particularly in handling cases of corruption and abuse of power. The purpose of this research is to examine the position of Polri investigators in their authority to handle the case and to identify the obstacles they face. The normative juridical research method used in this research uses primary and secondary data. The results of the study show that the position of Polri investigators is based on the concept of values or basic ideas for the establishment of the Criminal Procedure Code which requires conducting professional investigations and meeting the demands of the general court. This position is regulated in Law Number 2 of 2002 concerning the Indonesian National Police and Law Number 8 of 1981 concerning Criminal Procedural Law. Obstacles faced by Polri investigators in their authority to handle cases of corruption and abuse of authority include: confusion and contradictions in the interpretation of the Corruption Eradication Law, wrong understanding of the law by law enforcement officials, and limited infrastructure and information technology. This research provides important insights into the role and challenges of Polri investigators in the criminal justice system in cases of corruption and abuse of power.